Transformasi Politik di Indonesia: Analisis terhadap Peran Media Sosial dalam Partisipasi Politik Generasi Muda - Fajri, Nurul; Fajri, Raihal; Sulisawati, Novi; Helmi, Helmi (Journal of Political Sphere, 2024)
This study explores the role of social media in youth political participation in Indonesia. In this digital age, social media has become an important platform for young people to engage in political issues and the democratic process. This research employs a qualitative method with a descriptive-analytic approach. Data was collected through in-depth interviews, focus group discussions (FGDs), and social media analysis. The findings demonstrate that social media holds immense potential to enhance youth political participation. Social media provides an easily accessible and inexpensive platform for young people to access information, engage in discussions, and connect with others who share similar political interests. However, the use of social media for political participation is also accompanied by challenges. The spread of misinformation and disinformation, the misuse of social media for political gain, and limited access pose obstacles that need to be addressed.This study recommends improving youth media literacy, fostering constructive dialogue on social media, and strengthening social media regulations to maximize the potential of social media for youth political participation and minimize the existing challenges. This research opens up avenues for further studies on the long-term impact of social media on youth political participation, the influence of different social media platforms and content types, strategies for participation enhancement, case studies, and cross-country comparisons. Abstrak Penelitian ini mengeksplorasi peran media sosial dalam partisipasi politik generasi muda di Indonesia. Di era digital ini, media sosial telah menjadi platform penting bagi generasi muda untuk terlibat dalam isu-isu politik dan proses demokrasi. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif analitik. Data dikumpulkan melalui wawancara mendalam, dan analisis media sosial. Hasil penelitian menunjukkan bahwa media sosial memiliki potensi besar untuk meningkatkan partisipasi politik generasi muda. Media sosial menyediakan platform yang mudah diakses dan murah bagi generasi muda untuk mendapatkan informasi, berdiskusi, dan terhubung dengan orang lain yang memiliki minat politik yang sama. Namun, penggunaan media sosial untuk partisipasi politik juga diwarnai tantangan. Penyebaran informasi yang salah dan misinformasi, penyalahgunaan media sosial untuk kepentingan politik, serta keterbatasan akses menjadi hambatan yang perlu diatasi. Penelitian ini merekomendasikan peningkatan literasi media generasi muda, mendorong dialog yang konstruktif di media sosial, dan memperkuat regulasi media sosial untuk memaksimalkan potensi media sosial dalam partisipasi politik generasi muda dan meminimalisir tantangan yang ada. Penelitian ini membuka peluang untuk penelitian lanjutan mengenai dampak jangka panjang media sosial terhadap partisipasi politik generasi muda, pengaruh platform dan jenis konten media sosial yang berbeda, strategi peningkatan partisipasi, studi kasus, dan perbandingan lintas negara.